Konseling Individu Dengan Teknik Rational Emotive Behavior Therapy (Rebt) Dalam Meningkatkan Self Confidence Pada Remaja Korban Bullying - Putri Ayu Agusliana; Suryati Suryati; Emi Puspita Dewi (Scidac Plus, 2024)
A counselor organized individual counseling as a consultative service to address a problem the council is facing. Therefore, the counselor must be smart in determining a proper method to re-develop the self-confidence of adolescents who have become victims of bullying using the Rational Emotive Behavior Therapy (REBT) technique. This study aimed to raise confidence in “T” clients who suffered obesity bullying in Tulung Selapan Village. This research used a qualitative approach with a case study, where researchers drew information in depth from several sources. The data collection techniques used are interviewing, observation, and documentation. The results of this study showed that after conducting the counseling process, there were as many as four meetings in a month that used several stages of counseling implementation, namely, the initial stage, the intermediate stage, and the final stage. The process can give excellent results to the client, where the client